A Comprehensive Systematic Review and Meta-Analysis to Unravel the Noise-Dementia Nexus - Soonmyung A. Hwang; Aditi Singhvi; Lokesh Patil; Kimiya Gohari; Maayan Yitshak Sade; Elena Colicino; Melissa D. Aldridge; Andrea A. Baccarelli; Itai Kloog; Itai Kloog; Joel Schwartz; R. Sean Morrison; et al. (Public Health Reviews)
ObjectivesAs the aging population grows, Alzheimer’s disease and related dementias (ADRD) present a major public health challenge. Environmental noise, linked to stress and sleep disruption, may increase ADRD risk. We aimed to summarize the research literature on long-term noise exposure and ADRD.MethodsWe conducted a systematic review and meta-analysis of studies investigating the association of long-term (≥1 year) noise exposure and ADRD assessed with standardized diagnostic criteria. Two reviewers independently screened studies, extracted data, and assessed risk of bias. Eligible studies reported hazard ratios (HR) or similar effect estimates with confidence intervals.ResultsA multilevel random-effects meta-analysis of six longitudinal studies using 13 effect sizes found a significant association between long-term noise exposure and incident ADRD (HR: 1.15, 95% CI: 1.03–1.28). Interaction effects between noise source and dementia subtype were not statistically significant.ConclusionLong-term noise exposure may contribute to ADRD risk. Heterogeneity between studies highlights the need for standardized exposure assessment and consideration of other environmental factors. Future research should include the exposome approach for identifying environmental drivers of dementia.